PELATIHAN DAN PENDAMPINGAN PEMBUATAN VIDEO INTERAKTIF SEBAGAI MEDIA AJAR MENGGUNAKAN PROGRAM CANVA BAGI GURU SDIT AL-QONITA PALANGKARAYA - Pionera, Mutiarani; Elhawwa, Tazkiyatunnafs; Kartini, Nurul Hikmah (LPPM IAI Hasanuddin Pare-Kediri, 2023)
Given the implementation of online learning for elementary school-level children during the Covid-19 pandemic, teachers are required to: This community service activity aims to train and assist teachers in making interactive videos as presentation media for delivering teaching materials equipped with audio-visual content. The media used in the form of the Canva program, which is accessed by participants online (digital-based). To determine the achievement of this activity, data collection was carried out through two forms of instruments in the form of teacher peer assessment sheets and training participant satisfaction. The existence of peer assessment is intended to determine the enthusiasm of teachers in participating in training activities and their potential in developing digital-based teaching materials assessed from the perspective of peers. In addition, training participants' satisfaction instruments were needed to evaluate the overall implementation of activities, both from technical preparation and self-competence of the implementing team (pedagogic, professional, personality and social). The results of data processing showed that all teachers were very enthusiastic in participating in this training activity according to the assessment of their peers, and as many as 79% of participants were very satisfied with the training that had been provided. Each indicator that reflects the 4 forms of competence of the implementing team including pedagogic, professional, personality and social competencies is considered successful in achieving the objectives of this training, namely so that teachers can use presentation media equipped with audio-visual content to deliver subject matter to their students.